Body mass changes and nutrient intake of Optimist class sailors on a race day - Tan, B.; Sunarja, F. (Journal of Sports Sciences, 2007)
Young sailors tend to compete under a similar racing format to that of adults, spending extended hours exposed to the elements. This descriptive study measured the body mass changes in 65 male Optimist dinghy sailors (mean age 11.6 years, s = 1.4; body mass 37.2 kg, s = 8.2) and describes their fluid and carbohydrate intake during a typical race day. The sailors were weighed before launching and upon return to shore, and were interviewed to assess their fluid and carbohydrate intakes. After spending 6 h afloat, the participants displayed a mean weight loss of 0.5 kg (s = 0.6), indicating dehydration of 1.3% (s = 1.2, range -0.9 to 6.2%) assuming euhydration before they went afloat. Water loss amounted to 1.3 litres (s = 0.8) or 0.2 litres · h-1 (s = 0.1). Thirty-nine boys (60%) incurred <1% dehydration, 13 (20%) incurred 1 - 2% dehydration, and 13 (20%) incurred >2% dehydration. While afloat, the participants drank 816 ml (s = 621) of fluid, replacing only 61% of their water loss: 3% drank nothing, 78% drank plain water, and 15% drank sports drinks. Pre-race carbohydrate consumption was 1.7 g · kg-1 (s = 1.4, range 0.0 - 7.6 g · kg-1), with consumption when afloat of 7.1 g · h-1 (s = 6.9). In view of the hypohydration demonstrated, it is recommended that specific strategies be developed to improve the dietary practices of young sailors.